A Moderated Mediation Model of Wellbeing and Competitive Anxiety in Male Marathon Runners - Jose C. Jaenes; David Alarcón; Manuel Trujillo; María del Pilar Méndez-Sánchez; Patxi León-Guereño; Dominika Wilczyńska (Frontiers in Psychology, 2022)
Running marathons is an increasingly popular activity with an ever-increasing number of events and participants. Many participants declare that they pursue a variety of goals by running, namely, the maintenance of good health, the development of strength and improvement of fitness, the management of emotions, and the achievement of resilience and psychological wellbeing (PWB). The research has examined marathon running, like many other sports, and has studied various factors that reduce athletic performance, such as the experience of anxiety, and that enhance such performance, such as an increase in general wellbeing. This article reports the results of a study on the experience of competitive anxiety among 238 male marathon runners who participated in Seville’s (Spain) 26th Marathon race on February 23, 2020, and investigates the relationship between anxiety and key dimensions of wellbeing as measured by the Spanish-adapted 20-item PWB Scale. We hypothesized that participating athletes who rated high on the dimensions of PWB would experience lower levels of competitive anxiety with respect to this race. We also proposed that PWB would function as a mediating factor with respect to the experience of anxiety. The results show, as hypothesized, that marathon running enhances wellbeing and reduces anxiety. The data showed significant negative correlations between four of five wellbeing dimensions and the three types of anxiety measured, namely, somatic anxiety, worry, and concentration-impairing anxiety. Other findings supported our hypothesis that wellbeing, as measured, functions as a mediating factor for the moderation of competitive anxiety. Generalization of these findings is limited by the fact that the low number of female participants recruited did not permit valid statistical analyses in this respect. It is known that both anxiety and wellbeing are subjects to variation by gender. The future inclusion of male and female subjects in equivalent studies will undoubtedly add valuable information concerning the dynamics of anxiety and wellbeing. The implications of these findings and the limitations of the study will be discussed.